A self‐consistent approach to describe unit‐cell‐parameter and volume variations with pressure and temperature. Issue 6 (27th October 2021) - Angel, Ross; Mazzucchelli, Mattia; Gonzalez-Platas, Javier; Alvaro, Matteo
Abstract : A method is presented for the self‐consistent description of the variations of unit‐cell parameters of crystals with pressure and temperature. Abstract : A method for the self‐consistent description of the large variations of unit‐cell parameters of crystals with pressure and temperature is presented. It employs linearized versions of equations of state (EoSs) together with constraints to ensure internal consistency. The use of polynomial functions to describe the variation of the unit‐cell angles in monoclinic and triclinic crystals is compared with the method of deriving them from linearized EoSs for d spacings. The methods have been implemented in the CrysFML Fortran subroutine library. The unit‐cell parameters and the compressibility and thermal expansion tensors of crystals can be calculated from the linearized EoSs in an internally consistent manner in a new utility in the EosFit7c program, which is available as freeware at http://www.rossangel.net .